Masjid Abidin, Kuala Terengganu, Terengganu, 1793 - Soomro, Ali Raza; Hj Mohd Ariffin, Noor Aziah (ATSA Architects Sdn Bhd., 2016)
The Abidin Mosque is one of the oldest mosques in Terengganu and is strategically located in the centre of Kuala Terengganu town, within the proximity of many businesses, commercial and trading entities. The Abidin Mosque was originally constructed in 1793, and was established by Sultan Zainal Abidin Ibni Almarhum Sultan Mansur Riayat Shah (Sultan Zainal Abidin II). The mosque is more than 200-years-old. Currently, it is being renovated to accommodate around 2,500 people in a single prayer session.